Guidance Note on Jobs and Growth Issues in Surveillance and Program Work : Supplement on Country Case Studies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This supplement provides case studies of how countries around the world have addressed jobs and growth challenges, and how Fund staff have helped in this. The studies are meant to provide cross country experience. They share a broad structure, organized around four questions: ? What was the initial situation regarding growth, employment, and income distribution? ? What policy measures were implemented to enhance growth and employment and to even out the distribution of income? Were potential complementarities or trade-offs between enhancing growth, employment, and income distribution considered? ? How did Fund staff help the authorities? For example, in which areas did staff help the authorities analyze issues, how did staff go about analyzing issues, and what were the main considerations that shaped staff's recommendations? ? What were the results of policy actions taken?
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet